ROLE OF AGNIKARMA IN THE MANAGEMENT OF TRIGGER FINGER - V. Shekokar, Anantkumar; M. Borkar, Kanchan (International Journal of Ayurveda and Pharma Research, 2015)
Although in ancient times, Agnikarma practice has been very less but the last ten years have seen a remarkable rise in the efficiency of Agnikarma practice. This has been possible due to a combination of valuable researches and conferences carried out all over the globe. And thats the reason why most of the Ayurvedic Shalya Tantra practitioners use Agnikarma as a healing mechanism for most of the human diseases. Although modern surgical procedures are effective for curing diseases but the complications that arise out of such procedures are equally fatal and deadly. However in recent times it has been observed that such diseases can be cured by Agnikarma without undertaking any surgical procedure hence Agnikarma is proved to be a boon for curing such diseases. Trigger finger, a disease is commonly seen in professions which involve frequent movement of fingers e.g. surgeons, typist, barbour, soldiers, farmer etc. As the reference of Acharya Sushruta suggests the disease trigger finger can be correlated with Snaya Asthi Sandhi Aashrita Vikara. So the patient should be kept under Agnikarma therapy upto a satisfactory level of relief from pain and hence in this study a case of trigger finger was treated by Agnikarma for a period of 30 days. In this period 4 sittings was administered at intervals of 7 days giving a complete relief from symptoms. After completion of Agnikarma, the patient was followed up and observed for recurrence for 3 months.